The German “special representative” and corporate governance corporate governance for crisis situations in financial institutions - Eric Fiedler, Bernhard Thor (Centre for Law and Society, 2026)
In Germany, banks and insurance companies are regulated and supervised by the finan cial supervisor, the Bundesanstalt für Finanzdienstleistungsaufsicht [BaFin]. The Bank ing Supervision Act Kreditwirtschaftsgesetz [KWG] and the Insurance Supervision Act Versicherungsaufsichtsgesetz [VAG] provide the financial supervisor with a broad range of powers regarding the enforcement of the law. One of these powers is the ability to appoint a special representative. Under certain circumstances, according to s 83a (1) VAG, the financial supervisor is allowed to suspend parts or even whole organs of a supervised company and to replace them with a special representative.